The Health Burden of Orphan Zoonotic Disease in the United Kingdom, 2005–2009. (28th February 2013) - Halsby, K. D.; Walsh, A. L.; Smith, R.; Said, B.; Kirkbride, H.; Smyth, B.; Browning, L.; Larkin, L.; Morgan, D.
Summary 'Orphan' zoonotic diseases attract disproportionately low scientific and public health attention for the impact that they can have. This article pulls together information on their health burden in the UK from routine and enhanced data sources. These diseases are heterogeneous in nature; some have very low case numbers (e.g. hydatid disease), whilst others affect hundreds of patients each year (e.g. toxoplasmosis). The number of deaths attributed to orphan zoonoses is relatively low, and the majority recorded in this article were caused by toxoplasmosis. There is a clear issue of under‐reporting and under‐diagnosis in the data sets presented, and further work should be carried out to obtain more accurate estimates of the prevalence of zoonotic infections. Joint human and veterinary studies are especially important for these diseases.